1992
DOI: 10.1007/bf00185612
|View full text |Cite
|
Sign up to set email alerts
|

Collagen production by human smooth muscle cells isolated during intestinal organogenesis

Abstract: The extracellular matrix influences organogenesis by modulating cell behavior. In humans, collagen is the major matrix constituent of the adult intestinal wall and is synthesized by smooth muscle cells. The objective of the current study was to examine collagen production by fetal human intestinal smooth muscle cells isolated during intestinal morphogenesis. Techniques were developed for the isolation and culture of human fetal intestinal smooth muscle cells. The cultured cells were confirmed as muscle by immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

1995
1995
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 35 publications
0
17
0
3
Order By: Relevance
“…A variety of studies indicate that SMCs are capable of responding to and modifying their microenvironment by the secretion of cytokines, growth factors, and extracellular matrix (Simon-Assman et al, 1990Burgess and Sizeland, 1990;Simo et al, 1991;Perr et al, 1992; One such transcript, identified as T2 (arrowhead), was differentially expressed in immature smooth muscle myocytes in three separate reactions composed of multiple concentrations of distinct tcRNA preparations both in the presence and absence of DNAse 1. Pauly et al, 1992;Arciniegas et al, 1992;Mitchell et al, 1993;Glukhova et al, 1993;Thyberg and HulthardhNilsson, 1994;Skehel et al, 2000;Weir et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of studies indicate that SMCs are capable of responding to and modifying their microenvironment by the secretion of cytokines, growth factors, and extracellular matrix (Simon-Assman et al, 1990Burgess and Sizeland, 1990;Simo et al, 1991;Perr et al, 1992; One such transcript, identified as T2 (arrowhead), was differentially expressed in immature smooth muscle myocytes in three separate reactions composed of multiple concentrations of distinct tcRNA preparations both in the presence and absence of DNAse 1. Pauly et al, 1992;Arciniegas et al, 1992;Mitchell et al, 1993;Glukhova et al, 1993;Thyberg and HulthardhNilsson, 1994;Skehel et al, 2000;Weir et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Deletion mutations in two of the six collagen type IV subunits have been shown to result in Alport syndrome as well as diffuse leiomyomatosis (74). Collagen type IV, a critical component of basement membrane, has been postulated as important in the normal development of smooth muscle tissues (75,76). Therefore, defects in its structure may result in a higher incidence of developmental miscues resulting in smooth muscle tumor formation.…”
Section: Discussionmentioning
confidence: 99%
“…The preparation and specificity of these antibodies has been previously demonstrated [10]. Since the architecture of the human intestine is established by 20 weeks' gestation [17], studies were performed on tissues from 15 to 24 weeks' gestation. Human and murine intestine were stained according to standard procedures using hematoxylin as a counterstain and vgr-1 antibodies at 2 mg/ ml [10,18].…”
Section: Antibody Production and Immunohistochemistrymentioning
confidence: 99%
“…Intestine was obtained from 11-to 24-week human abortuses as previously described [17]. The research protocol was approved by the Committee on Human Research of the University of California according to the policies of the National Institutes of Health.…”
Section: Cell Isolation and Culturementioning
confidence: 99%
See 1 more Smart Citation